Synergetic effect between Pd2+ and Ir4+ species promoting direct ethane dehydrogenation into ethylene over bimetallic PdIr/AC catalysts. Issue 12 (9th May 2022) - Zhang, Ling; Sun, Jikai; Jiang, Shuchao; He, Huijie; Ren, Guoqing; Zhai, Dong; Tu, Rui; Zhai, Shengliang; Yu, Tie
Abstract : This work reported the efficient Pd–Ir pairs on the Pd7Ir2/AC-B catalyst achieved a TOF (C2 H4 ) of 756.6 h −1 at 500 °C, and the direct ethane dehydrogenation (EDH) rationale and deactivation mechanism were proposed. Abstract : This work reported an efficient PdIr/activated carbon (PdIr/AC) catalyst and its application during direct ethane dehydrogenation (EDH) into ethane. The XRD and HADDF-STEM results revealed Pd/Ir nano-particles and atomically dispersed Pd 2+ and Ir 4+ species simultaneously. The activity tests demonstrated that Ir species showed higher C2 H4 selectivity than Pd species and the co-presence of Pd/Ir could further improve the catalytic stability and inhibit carbon deposition over the bimetallic Pd/Ir catalyst. Nevertheless, raising the reaction temperature from 500 °C to 600 °C boosted coking including carbon nanotubes (CNTs) and carbon particles. XPS results of Pd7Ir2/AC-B after Ar or H2 pretreatment proved that the active sites are Pd 2+ /Ir 4+ species. The simulation results exposed the reaction pathway over Ir 4+ /Pd 2+ species, and ethane dehydrogenation was the rate-determining step over the PdIr/AC sample; meanwhile, the synergetic effect between Pd 2+ and Ir 4+ increased their TOF (C2 H4 ). Finally, a deactivation mechanism was also proposed to examine the coking over various metal species.